PENGENDALIAN HAMA Spodoptera exigua Hubner. PADA TANAMAN BAWANG MERAH VARIETAS LEMBAH PALU DENGAN PENGGUNAAN PUPUK DAN MULSA - Valentino Valentino; Abd. Rahim Thaha (Universitas Tadulako, 2019)
This study aimed to determine the effect of fertilizer and mulch on the intensity attack of S. exigua and the yield of Lembah Palu shallot variety. The research was conducted in Bolu Pountu Jaya, Sigi Village, District of Sigi Biromaru, Sigi Regency, from September to November 2013. The study design was a two-factorial randomized pattern with three replicates for each experimental unit. The first factor was various types of mulch consisted of four treatment without mulch (M0), rice straw mulch (M1), cocoa mulch (M2) and plastic mulch (M3). The second factor was different kinds of fertilizers including liquid organic fertilizer (P1), guano fertilizer (P2) and synthetic fertilizer (P3). There is no significant interaction effect between the type of fertilizers and mulch on the intensity of S. exigua and shallot yields. However, the individual effect of the mulches was significant on reducing the intensity of S. exigua attack and increasing the yield of the shallot. The rice straw mulch reduced the attack intensity of S. exigua by 20.83 %, whereas the cacao mulch increased the yield by 47.61 % compared to the control treatment. Keywords : Fertilizer, Lembah Palu shallot, mulch and Spodoptera exigua.